Planning and developing a talent pool of grassroots-level cadres from ethnic minority groups in the western region of Nghe An province - Phan Van Tuan; Nguyen Khanh Ly (Journal of State Management, 2025)
This article focuses on analyzing the current planning status and developing a talent pool ofgrassroots-level cadres from ethnic minority groups in the Western region of Nghe An province. Basedon the analysis, the article proposes several measures to enhance the effectiveness of cadreplanning and development, particularly for grassroots-level cadres from ethnic minorities. The ultimate goal is to build a contingent of ethnic minority cadres with an appropriate quantity, suitable structure, and full qualifications in terms of ethics and competence, thereby contributing to the sustainable development of the Western region of Nghe An province.